(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The paper focuses on the relationship between International Law and International Relations, i.e. on their interconnectedness as a substantial issue both from theoretical and practical point of view. The starting premise is that although they constitute distinct academic disciplines, the objects of their interest can hardly be analysed in isolation from each other. Even those who disagree with the thesis of their academic synergy, acknowledge that with no international law there could be no international relations; also, the practice of international politics is a ground that breeds international legal norms. In the analysis of this rather complex relationship, a special emphasis is placed on the need for deconstruction of the wide-spread myth that international law is by default ‘good’ (i.e. positive in a normative sense of the word), while the international politics is to be blamed for all the bad things that happen in the international arena. Instead, we make an attempt to shed some light on the most important strategic and moral limits of the international law, in order to induce a more critical viewpoint on the relations between power, politics and law in the international arena. The paper ends with some suggestions about the need for development of an innovative research agenda in elaboration of this relationship.